The Insomniacs. - David Kushner (IEEE spectrum)
At the heart of Sony's new Playstation 3 (PS3) gaming console is the powerful new Cell Broadband Engine microprocessor, which is capable of doing up to 192 billion floating-point operations per second. The biggest challenge for game developers at Insomniac is programming the Cell to create addictive and eye-popping PS3 games that showcase the power of the new processor. Packing nine processors onto a single chip, the Cell's real brain resides in the power processor element (PPE) which organizes, schedules, and doles out tasks to the eight processors, preferably in the most efficient way. The eight remaining processors are known as the synergistic processor elements (SPE) and are specially designed to do the kind of fast but not necessarily precise calculations needed for multimedia tasks. For the game developers at Insomniac, the PS3 game has been a metagame of experimentation. With the added muscle power of the cell, they hope to come up with some of the best new game play experiences ever